2019
DOI: 10.1016/j.jval.2019.09.354
|View full text |Cite
|
Sign up to set email alerts
|

Pcn158 Patient Burden and Costs for the Treatment of Multiple Myeloma in Finland in 2009-2016, Using Multiple Data Sources: An Electronic Hospital Database, Medical Chart Review, and Interviews With Healthcare Professionals

Abstract: for therapeutic regimen derived from GALLIUM and PRIMA clinical trials: in particular, progression-free survival (PFS), early progressive disease (PD), and treatment duration (TTOT) were extrapolated by fitting parametric distributions on empirical data in GALLIUM, whilst late PD on data in PRIMA, due to immature data in GALLIUM. PD state was split in early (progression within 2-years) and late since patients progressing early have much poorer survival outcomes than those progressing later. Expected survival w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In some European countries and the United States, the treatments received by patients for MM and other comorbidities have a substantial impact on costs, which can often be greater than the patients' ability to pay. The often-unmet financial needs of patients with MM can moderate the relationship between psychological morbidity and HRQOL [32,35,36]. In the United States, a study of 160 patients with RRMM found that treatment copays and the costs associated with visits to the clinic contributed the greatest burden to overall costs [32].…”
Section: Cost To Patientsmentioning
confidence: 99%
See 3 more Smart Citations
“…In some European countries and the United States, the treatments received by patients for MM and other comorbidities have a substantial impact on costs, which can often be greater than the patients' ability to pay. The often-unmet financial needs of patients with MM can moderate the relationship between psychological morbidity and HRQOL [32,35,36]. In the United States, a study of 160 patients with RRMM found that treatment copays and the costs associated with visits to the clinic contributed the greatest burden to overall costs [32].…”
Section: Cost To Patientsmentioning
confidence: 99%
“…A Portuguese cross-sectional study (N=124) found that 91.9% of previously treated patients with MM reported an unmet financial need, and when financial needs were higher, there was a negative relationship between psychological morbidity and HRQOL [35]. In Finland, an observational study assessed MM-related health care resource use and costs in patients with "active" MM (N=97) treated between 2009 and 2016 [36]. An average travel distance of 35.4 km (approximately 22 miles) was reported for health care visits, which placed a substantial financial burden on patients as the mean per-patient travel costs per 28 days ranged from €75.13 (US $76.42) to €447.99 (US $455.68) [36].…”
Section: Cost To Patientsmentioning
confidence: 99%
See 2 more Smart Citations